Implementasi Model PROGRAM dan Media Fraction Makers untuk Meningkatkan Keterampilan Berpikir Kritis dan Kolaborasi - Seman, Ahmad; Pratiwi, Diani Ayu (CV. ITTC INDONESIA, 2024)
The problem in this study is the lack of critical thinking skills, collaborative skills and difficulty in working on the evaluation of fragmented material in students of 4th grade SDN Andhika. The alternative to solving the problem is to implement learning using the PROGRAM model which is a combination of the learning model Problem based learning, Group Investigation, Two Stay Two Stray and Team Game Tournament. The study aims to analyze improved critical thinking skills and student collaboration. This research uses a qualitative research approach with the type of Class Action Research, which is carried out with four meetings. The subjects of this study are students of the fourth grade SDN Andhika school year 2023/2024 which totaled 13 students consisting of 6 males and 7 females. The type of data in this research is both qualitative and quantitative data. The results of this study showed that students' critical thinking skills improved with the criteria of